Milking Management Practices Followed In Selected Areas of the Kottayam District of Kerala State - Bimal P. Bashir and Vinod Kumar G. (J Life Sci, 2013)
A survey was conducted to study milking management practice followed by 60 dairy farmers with average herd size of 7.25, majority of them rearing crossbred cattle in the Kottayam district of Kerala state (2010 - 2011). Majority (73.33%) of dairy farmers were following full hand method, 18.33 per cent and 8.33 per cent were following knuckling and machine milking respectively as method of milking. All the dairy farmers were practicing two times milking a day; none of the dairy farmers was following three times milking schedule. About 68.33% of dairy farmers were practicing udder massaging and feeding concentrate and 31.66 percent were practicing calf suckle reflex for let down of the milk. Only 11.67% of the dairy farmers milking their animals in separate and dry places however all farmers were regularly cleaning milk utensils and washing udder before milking as clean milk production practice. The study indicates milking management practice in majority of the dairy farmers is satisfactory but there is a scope for further improvement in milk production practices by creating awareness.